Potensi Ekstrak Etanol Daun Keladi Tikus (Typhonium flagelliforme Lodd.) Sebagai Induktor Apoptosis Sel Kanker Lidah Manusia (SP-C1) - Himmaturojuli Rosyid Ridlo; Supriatno Supriatno; Ana Medawati; Atiek Driana Rahmawati (Universitas Muhammadiyah Yogyakarta, 2012)
Typhonium flagelliforme Lodd has been used traditionally to cure breast cancer, lung, colon, rectum, liver, prostate, kidney, cervix, throat, bone, brain, spleen, bladder, leukimia and pancreas cancer. The ethanolic extract of Typhonium flagelliforme Lodd contained active compounds that could inhibit cancer cell growth. One of the active compounds was saponin and phenolic. The aim of study was to examine the potency ethanolic extract of Typhoniumflagelliforme Lodd. as inductor of apoptosis in human oral tongue cancer cell Supri's Clone-1 (SP-C1). The desingn of used in this study was pure laboratoris experimental with human oral tongue cancer cells line (SP-C1) as a sample which treated by ethanolic extract of Typhonium flagelliforme Lodd in various concentrations (0, 25, 50, 75, 100, 125 µg/ml) for 48 hours. Apoptosis examination was carrried out by painting with etidium bromide-acridin orange. The result of the study showed that etanolic exstract of Typhonium flagelliforme Lodd. induced apoptotic SP-C1 cell line. Statistical analisis with One Way Anova revealed etanolic extract in various concentration have significant differences (P=0,00) after treated with etanolic extract Typonium flagelliforme Lodd. It also found that the most effective concentration inducing apoptosis of human tongue cancer cells Supri's Clone-1 (SP-C1) was the 125 µg/mL. The conclusion of this research, ethanolic extract of Typhonium flagelliforme Lodd. has a potency to induce apoptosis human oral tongue cancer cells (SP-C1).